Morphology and surface structure of eggs and first instar larvae of Croce schmidti (Navás, 1927) (Neuroptera: Nemopteridae) - Satar Ali̇; Suludere Zeki̇ye; Candan Selami̇; Canbulat, Savaş (Zootaxa, 2007)
The morphology of eggs and first instar larvae of Croce schmidti (Navás, 1927) is described and figured for the first time using light and scanning electron microscopy. The females were collected from Derik, Mardin Province, Turkey and maintained in the laboratory. The eggs are elongate and cylindrical with rounded ends and bear a small terminal micropylar knob. Except for the adhesive materials, the chorion surface is smooth. The newly emerged larva of C. schmidti is characterized by a slightly quadrangular head and short prothorax and has prominent pale dark brown color markings on the metatergites. The body is covered with short brown setae, which include macrotrichia and dolichasters.